The Transformative Power of Collaborative Inquiry Realizing Change in Schools and Classrooms. - Donohoo, Jenni Anne Marie (SAGE Publications, 2016)
Foster reflective teacher leadership and make real change happen! Teachers are powerful change agents in the on-going process of school improvement. This insightful, must-read companion guide to Donohoo's best-selling Collaborative Inquiry for Educators helps school leaders develop a sustainable professional learning culture. Practical suggestions and in-depth research shed light on your path as you explore the benefits and challenges of adopting authentic teacher collaboration across schools and districts. Learn valuable lessons from leaders in the field and discover: A rationale and framewo.